2006
DOI: 10.1002/chp.72
|View full text |Cite
|
Sign up to set email alerts
|

Clinical teachers' attitudes toward the efficacy of evidence-based medicine workshop and self-reported ability in evidence-based practice in Iran

Abstract: An EBM workshop may improve clinical teachers' abilities and skills in using EBM. However, carefully designed studies are required to evaluate the long-term effects of EBM curricula in changing behaviors, practice patterns, and patient care outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…However, the realist approach [42] described in our report was necessary, given the multiple complexities of implementing a programme like this in a resource-poor country where financial support was limited to travel expenses for faculty teaching the course. The magnitude of the effect size in this report was similar to a study done in Iran; in two half-day workshops conducted in the same year, the self-reported EBM skills increased from 3.1 to 4.4 (using a 5-point Likert scale) and the attitudes towards EBM were unchanged [43]. The results of an ongoing cluster-randomized clinical trial on an integrated reproductivehealth electronic learning EBM programme are not yet available [12].…”
Section: Challenges and Lessons Learnedsupporting
confidence: 80%
“…However, the realist approach [42] described in our report was necessary, given the multiple complexities of implementing a programme like this in a resource-poor country where financial support was limited to travel expenses for faculty teaching the course. The magnitude of the effect size in this report was similar to a study done in Iran; in two half-day workshops conducted in the same year, the self-reported EBM skills increased from 3.1 to 4.4 (using a 5-point Likert scale) and the attitudes towards EBM were unchanged [43]. The results of an ongoing cluster-randomized clinical trial on an integrated reproductivehealth electronic learning EBM programme are not yet available [12].…”
Section: Challenges and Lessons Learnedsupporting
confidence: 80%
“…For this reason, holding workshops on EBM and search strategies for clinicians, and including courses for the same in medical colleges, is essential. Most studies have recommended such courses in addition to further education on effective searching skills and use of proper keywords [16,20,22,[27][28][29][30][31][32][33]. Although EBM workshops and courses are now held by the Iranian Center for EBM, informing academic members and physicians about EBM and expanding the workshops appears essential.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about effective methods of teaching EBM skills in developing countries [23]. In medical schools in Jordan, EBM skills have not been yet included in undergraduate nor in postgraduate education.…”
Section: Introductionmentioning
confidence: 99%